Audio module to capture, store and reproduce sound - Leitón Jiménez, Jason Leitón-Jiménez (2021)
This poster explains the design of an audio module, which is capable of capturing sound signals and storing them for later reproduction. The development platform is an embedded system (Beaglebone black), which has GPIO pins for user interaction. One of the objectives of the module is to keep production costs low, so the electronic components will be chosen taking quality criteria in operation as well as their cost. In the software component, the fdatool tool will be use to design the digital filter, getting the differences equation. It should be noted two major challenges that the development of this project has are the presence of noise in the analog signal and the sampling frequency with which the samples are taken to obtain the digital signal.